Use case specifications: How complete are they?. Issue 1 (23rd August 2019) - Tiwari, Saurabh; Gupta, Atul
Abstract: The flexibility of the use cases in specifying requirements from informal textual descriptions to more formal ones makes them usable in different contexts and purposes. However, the versatility of use cases regarding their admissible structure raises a natural concern about the specification completeness. This paper reports on the analysis of the eight different variants of use case template regarding their functional completeness, ability to express the set of particular functionalities, by comparing their information contents exercised by comprehensive questionnaires on five different problem specifications. The questionnaire was obtained from two sources: one based on the understanding of the functionality to be implemented and the other based on the functionality documented in eight different use case templates under study. Our results suggested that use cases can be used to specify a complete set of requirements intended to develop a software system. We found that the choice of a use case template influences the completeness of the specification. A more detailed analysis of the eight different variants of use case template resulted in the identification of 21 significant use case elements. We showed that by incorporating these significant use case elements in a given template, the completeness of the specification could be further enhanced.